Comparison of Clinical Effectiveness of Folfirinox versus Gemcitabine on Quality of Life in Patients with Pancreatic Cancer Stage IV - Murtezani, Ardiana (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The aim of this study is to assess the clinical effectiveness of folfirinox (Fol) compared with gemcitabine (Gem) on quality of life (QOL) that predicts survival in patients with Stage IV of pancreatic cancer. Materials and Methods: A total of 34 patients suffering from metastatic pancreatic adenocarcinoma were randomized into two groups, the Gem group (n = 17) and Fol group (n = 17). The first group was treated with Gem in a dose of 1000 mg/m2 once weekly for 7 weeks, followed by 1 week of rest during the first cycle and subsequently 1000 mg/m2 once weekly for 3 weeks followed by 1 week of rest. The second group was treated with Fol (oxaliplatin 85 mg/m2, irinotecan 180 mg/m2, leucovorin 400 mg/m2, and fluorouracil 400 mg/m2 bolus, followed by 2400 mg/m2 on 46-h continuous infusion) once every 2 weeks. The QOL was measured by the functional assessment of cancer therapy (FACT)-hepatobiliary cancer scale. Results: Thirty-four of randomized patients completed the study, and there were no significant differences among the two groups at baseline demographic characteristics. Overall QOL, P value shows the significance of correlation for components of FACT in all scales between Fol-group and Gem-group. Median survival time for the entire cohort was 14.1 months for Fol-group compared to Gem-group which was 9.2 months. P value shows the significance of the correlation between survival rate and stage of tumor, in Fol-group versus Gem-group (P = 0.0001). Conclusions: We conclude that Fol significantly improves QOL, physical functioning and survival time in advanced pancreatic cancer patients in comparison with Gem.